Influence of water security and its’ consumption on the health of market women in Oyo township, Nigeria - Olanrewaju, Oniyangi, Shuaib; Olaniy, Fagbamila, Sayofunmi; Anike, Adebowale, Grace; Ayodeji, Falusi, Bamidele; Omolara, Oyawole, Dorcas (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The influence of water security and its’ consumption on the health of market women in Oyotownship, Nigeria was investigated in this study. A descriptive research survey was adoptedand the population of the study comprised of all market women in Oyo township, Nigeria.Simple random and convenient sampling technique was used to select two markets and fourhundred (400) respondents. Structured questionnaire was used for data collection. PearsonProduct Moment Correlation was used for data analysis. A correlation coefficient of 0.73was obtained. Four postulated hypotheses were tested using inferential statistics of chisquare(X2) at 0.05 alpha levels. Results obtained showed that water security; volume ofwater consumed; water storage and water purification had significant influence on healthof market women. We therefore recommended that market women should be adequatelyeducated on the importance of water security and purification in order to guarantee betterhealthy living.